PENGEMBANGAN INSTRUMEN TES KETERAMPILAN SHOOTING PADA PEMAIN SEPAKBOLA USIA 16-20 TAHUN - Muhammad Taufik Aziz; Khoiril Anam (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
The goal of this project is to develop a talent test instrument for football shooting accuracy for soccer players between the ages of 16 and 20. Utilizing research and development techniques, this study was undertaken. 36 participants, 6 PS UNNES players, 18 PS POP players, and 16 PS Tunas Sakti Mandiri players, were used as subjects in this study. In this study, the validation was conducted out by soccer course instructors, a professional club coach from the Indonesian 3rd League, and three coaches from the research sample clubs who were registered at the PSSI Ascot in Semarang city. The validity test uses content validity. The football shooting accuracy test, according to experts, falls into the